PERANAN KREATIVITAS TERHADAP HASIL BELAJAR NAIL ART TIGA DIMENSI PADA MAHASISWA PROGRAM STUDI TATA RIAS AKS-AKK YOGYAKARTA - Helmia Cipta rohmawati; Ika Prasetyani Pambudi (Jurnal Socia Akademika, 2023)
This study aims to determine how vital student creativity is in three-dimensional nail art learning and its influence on their learning outcomes. The method used is a survey method with correlational techniques. The population used in this study is students of the cosmetology study program class 2022 who are taking courses or learning three-dimensional nail art. The number of samples taken was 25 students. The results of three-dimensional nail art learning in this study are the total scores obtained by students in learning three-dimensional nail art practice and theory and filling out questionnaires. The relationship between creativity (X) and three-dimensional nail art learning outcomes (Y) is linear. Thus this regression equation model can be used to predict. The study results stated that creativity in three-dimensional nail art learning has a role in improving student learning outcomes. Therefore, learning outcomes will also increase to 84%.